2019
DOI: 10.1002/2211-5463.12623
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐222 promotes colorectal cancer cell migration and invasion by targeting MST3

Abstract: Metastasis is one of the major causes of death in colorectal cancer (CRC) patients. MiR‐222 has been reported to be an oncogene in many types of cancer. However, its role in CRC cell invasion and migration as well as CRC downstream signaling pathways remains largely unknown. Our study found that miR‐222 overexpression promotes the migration and invasion of CRC cell lines, and miR‐222 interference results, as expected, in inhibition of migration and invasion. Bioinformatic analysis and dual luciferase reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…MicroRNAs (miRNAs/miRs), composed of 19-25 nucleo-/miRs), composed of 19-25 nucleo-miRs), composed of 19-25 nucleotides, are a group of short non-coding endogenous RNA molecules that function as negative regulators on gene expression via binding to the 3' untranslated regions (3'UTRs) of target mRNAs (9,10). Accumulating evidence has suggested that miRNAs are extensively involved in tumor development by participating in biological processes, including cell proliferation, apoptosis, migration and invasion, especially in CRC (11)(12)(13). miR-133a-3p, a member of the miRNA family, has been recently studied for its tumor suppressive role in various cancer types by targeting different related molecules.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs), composed of 19-25 nucleo-/miRs), composed of 19-25 nucleo-miRs), composed of 19-25 nucleotides, are a group of short non-coding endogenous RNA molecules that function as negative regulators on gene expression via binding to the 3' untranslated regions (3'UTRs) of target mRNAs (9,10). Accumulating evidence has suggested that miRNAs are extensively involved in tumor development by participating in biological processes, including cell proliferation, apoptosis, migration and invasion, especially in CRC (11)(12)(13). miR-133a-3p, a member of the miRNA family, has been recently studied for its tumor suppressive role in various cancer types by targeting different related molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The AKT signaling pathway also proved to play a role in miR-222-mediated invasion and metastasis of papillary thyroid cancer [220]. As in colon cancer, miR-222 proved to enhance the formation of lung metastasis in thyroid cancer patients [219,220].…”
Section: Mir-222mentioning
confidence: 94%
“…MiR-222 alters the colon cancer cell migration through the downregulation of its target gene mammalian STE20-like protein kinase 3 (MST3) which plays a key role in the phosphorylation of paxillin, thus reducing the intercellular adhesion. Furthermore, miR-222 together with MST3 play a crucial role in the production of inadopodia [219]. Furthermore, the overexpression of miR-222 in aggressive papillary thyroid cancer tissues was established.…”
Section: Mir-222mentioning
confidence: 98%
“…In colorectal cancer (CRC), miR-222 overexpression increased the migration and invasion of CRC cell lines ( 37 ). miR-29a-3p and miR-200a served as targets for Astaxanthin (AXT), one of the most common carotenoids ( 38 ).…”
Section: Microrna (Mirna) In Invadopodiamentioning
confidence: 99%